Novos mares, novos olhares: o percurso de Angela Lago do livro ao site - Santos, Maria Andrade dos (2010)
Having as initial objective to unmask the literature in the Internet, we cover the way of discovery through the Angela Lago’s workmanships: books and site. From this passage book to site, we can evidence that Angela Lago writer trod the way of the intertextuality, the visual and verbal overlapping, hypertext, a way that certainly would take it and it took it to the site. A site, as much others, where we can find image, sound, movement, and tridimensionality form, but this is what we can also find in her books, books with pictures/color/movement, words/sound. Showing the non-linear or multilinear form in the books, and the linear form on the site. For this dissertation we use the books: O Fio do Riso, and Chiquita Bacana e outras pequetitas.